1984
DOI: 10.1038/307127a0
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence of the maize transposable element Dissociation

Abstract: The DNA sequence of the terminal 4.2 kilobases (kb) of the 30-kb insertion in the endosperm sucrose synthase gene of maize mutant sh-m5933 shows that it comprises two identical 2,040-base pair (bp) segments, one inserted in the reverse direction into the other. We suggest that the 2,040-bp sequence is an example of the transposable element Dissociation described by Barbara McClintock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(62 citation statements)
references
References 18 publications
1
58
0
3
Order By: Relevance
“…Composite Ds elements are made of more than one Ds. The only fully sequenced composite Ds is the chromosome breaker element in allele sh-m5933 (9,33). It is composed of two completely identical, simple deletion Ds elements in reverse orientation and of the 8-bp host duplication which flanks the internal element.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite Ds elements are made of more than one Ds. The only fully sequenced composite Ds is the chromosome breaker element in allele sh-m5933 (9,33). It is composed of two completely identical, simple deletion Ds elements in reverse orientation and of the 8-bp host duplication which flanks the internal element.…”
Section: Resultsmentioning
confidence: 99%
“…There are six fully sequenced Ds elements, all of which share with Ac nearly identical TIRs and fall into the following four categories: (i) those with nearly no similarity to Ac, like Ds1 (57); (ii) elements with highly similar subterminal regions but with internal deletions, like Ds9 (46); (iii) double Ds elements where one internally deleted Ds is inserted into another identical Ds in an inverted orientation (9); and (iv) Ds elements that contain both deletions and insertions in the internal part of the element, like Ds2 (40) and the Ds element in WxB4 (60). While double Ds elements can be interpreted as transposition of one element within the other (9), the mechanism of formation of other types of Ds elements is not known.…”
mentioning
confidence: 99%
“…The integration of excised Ds::HPT elements into the rice genome was demonstrated by analyzing Ds::HPT sequences in the hygromycin-resistant caUi which were obtained by culturing transfected protoplasts. In one-third of the resistant calli, the integration of excised Ds::HPTwas found and 8 bp direct repeats, which are produced as a consequence of duplication of a target site upon integration of Ac/Ds (D6ring et aL, 1984;Pohlman et aL, 1984;Sutton et aL, 1984), flanked the integrated Ds::HPT. The analysis of the empty target site sequence clearly showed that 8 bp direct repeats were produced upon integration of Ds::HPT.…”
Section: Discussionmentioning
confidence: 99%
“…Eight base pair direct repeats flank the Ds in five out of six calli. Because Ac/Ds elements induce duplication of a target site of 8 bp upon integration (D6ring et al, 1984;Pohlman et al, 1984;Sutton et aL, 1984), the 8 bp direct repeats observed here were likely to have been generated upon integration of Ds::HPT. This was verified by analyzing the integration site in untransformed rice DNA ( Figure 5).…”
Section: Transformation Of Rice Protoplasts By Ds::h Ptmentioning
confidence: 94%
“…Sequence analysis of the Ds-r deletion derivative trDs-228 showed the breakpoints of the deletion to be at small direct repeats. Also, Ac-derived Ds elements like Ds2 [18], Ds6 [22], Ds9 [44] and AcA [47] and deletion derivatives of the Drosophila P element [41] have small direct repeats at breakpoints. The mechanism which was used to explain the P deletion derivatives is 'double-strand gap repair' [24].…”
Section: The Generation Of Ds-r Deletion Derivativesmentioning
confidence: 99%